Differentiated Learning Strategies of Driving Teachers in Optimizing Students' Learning Interests in Elementary Schools - Muhibbuddin Muhibbuddin; Yulia Santi; Ety Mukhlesi Yeni (Al-Madrasah: Jurnal Ilmiah Pendidikan Madrasah Ibtidaiyah, 2026)
The implementation of differentiated learning strategies by the Leading Teacher in elementary schools lies in the diversity of characteristics, abilities, and learning interests of students that cannot be accommodated through a uniform learning approach. Through differentiated learning, the Leading Teacher plays a strategic role in creating student-centered learning so that student learning interests can be optimized sustainably. The purpose of this study is to analyze the implementation and impact of differentiated learning by the leading teacher in optimizing student learning interests in the core cluster 03 Bandar Baru, Pidie Jaya Regency. This study uses a qualitative method with a case study approach. The sample used was determined by purposive sampling consisting of 8 principals and teachers as respondents. Data collection techniques with interview and observation guidelines. Qualitative data validity tests include credibility tests, transferability (transfer value), dependability and confirmability. Data analysis was carried out using qualitative descriptive methods, namely data reduction, data presentation and conclusions. The results of this study indicate that the implementation of differentiated learning is carried out through grouping students based on learning abilities and interests, providing diverse activities, and choices in presenting and completing assignments. Teachers provide flexible support and create a learning environment that supports active student engagement. Differentiated learning has a positive impact on increasing student interest in learning. Students demonstrate increased interest in participating in lessons, increased attention during learning, increased awareness of the importance of learning, and optimal knowledge development.